Personal and Interpersonal Concepts Understanding of At-risk Adolescents and Parents in an Educational Environment - Widi, Muhammad Naufal; Noviarita, Heni; Saifudin, Muhammad; Yanti, Fitri (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2023)
The research employed the descriptive method. The data collecting techniques were interviews, observations, surveys, and focus group discussions with several elements of society from at-risk adolescents, parents in general, and community leaders. The results showed that people's knowledge was poor both personally and interpersonally. The researchers assessed the need for socialization planning involving the community. Also, the researchers socialized the adolescents with counseling on children's rights, social and assertive skills, helping skills, establishing a Children's Forum, and optimizing the Taman Baca Anak (Children's Reading Garden). Furthermore, a socialization of child protection and good parenting was carried out for parents. The organization can be strengthened by developing networks with the Bandar Lampung City Family Learning Center. The evaluation showed an increased empowerment of adolescents, parents, adults, and organizations. The practical implication of this research is the learning method in improving the level of thinking and proficiency in action for at-risk adolescents where every process involves the community. Within the scope of future research, there is an expectation that educational interventions will be employed to foster the comprehension of at-risk adolescents and their parents concerning the importance of adolescent self-awareness and the promotion of effective parent-child communication.